Insights from QM/MM-ONIOM calculations: the TADF phenomenon of phenanthro[9, 10-d]imidazole-anthraquinone in the solid state. Issue 36 (2nd September 2021) - Li, Huixue; Wang, Xiaofeng; Yuan, Kun; Lv, Lingling; Li, Zhifeng
Abstract : The QM/MM technique is employed to study the TADF phenomenon of a near-infrared molecule (PIPAQ) in aggregation state, the calculated results can prove the steric hindrance effect from the surrounding molecules. Abstract : In this paper, we employed first-principles methods and the QM/MM technique to study the thermally activated delayed fluorescence (TADF) phenomenon of a near-infrared molecule (PIPAQ) in vacuum, solution, and the aggregation state. Our calculated results show that (1) the cluster can decrease the energy gap between the first singlet excited state (S1 ) and the first triplet state (T1 ) compared with the monomer, furthermore, the T1 state and S1 state in the cluster are energetically closer to each other, which implies that the energy gap is smaller in comparison with that in solution and can promote the intersystem crossing (ISC) process due to the surrounding effect; (2) the optimally tuned range-separated functional is applicable to simulation of excited states and the outcomes are in good agreement with experimental values; (3) the reorganization energies associated with ISC and the reverse intersystem crossing (RISC) processes between the S1 and T1 states are sensitive to the calculated methods and the environments, and thus the following calculated ISC and RISC rates vary dramatically according to different reorganization energies; (4) all radiative and nonradiative rates are insensitive to temperature, but sensitive to environments, all the radiative rates increase in the cluster while the nonradiative rates decrease, which enhances the fluorescence quantum efficiency and agrees with the observed value. The above results demonstrate that the surrounding effects are very important for modulating the photophysical properties of the PIPAQ compound. Finally, this studied conclusion can give a helpful insight into the TADF mechanism for the title compounds, by which novel TADF materials with excellent performance could be rationally designed.